Tanggapan Nasabah atas Produk Perbankan : Studi Kasus di NISP Cabang Bogor - Tobung, Maju Lumban; Achmad, Noor (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2008)
The purpose of the research was to understand consumerâs responses to product policy taken by NISP Cabang Bogor in collecting fund from society. Samples were determined purposively which the number was 45 respondents. Data collected comprises 2 aspects, i.e. level of performance and level of importance, from 10 variables namely: (a) security, (b) ATM, (c) interst rate, (d) saving procedures, (e) services, (f) promotion, (g) strategic location, (h) branch offices, (i) accessibility, and (j) location security. The measurements of the data used LikertScale (1-5). The data was analysed using Boston Consulting Group Model which divides responses into 4 quadrants. The result of the research shows that the following variables are NISPâs strength points, namely: (a) security, and (g) strategic location. They need to maintain. Meanwhile, prioritized variables are: (c) to increase interest rate, (b) to increase the umber of ATM, (f) to enhance promotion and (i) to improve transportation access. Keyword: Product policy.